Partial Nephrectomy Versus Radical Nephrectomy for Clinical T2 or Higher Stage Renal Tumors: A Systematic Review and Meta-Analysis - Huang, Ruizhen; Zhang, Chiyu; Wang, Xing; Hu, Honglin (Frontiers in Oncology, 2021)
Objective The choice of surgical method for clinically diagnosed T2 or higher stage kidney cancer remains controversial. Here, we systematically reviewed and collected published comparative studies on renal function, oncologic outcomes, and perioperative results of partial nephrectomy (PN) versus radical nephrectomy (RN) for larger renal tumors (T2 and above), and performed a meta-analysis. Evidence Acquisition Following searches of PubMed, Web of Science, and Embase, the original studies on PN vs. RN in the treatment of T2 renal cancer were screened through strict inclusion and exclusion criteria. RevMan 5.4 was used for data analysis of the perioperative results, renal function, and oncologic outcomes of the two surgical methods for T2 renal tumor therapy. The weighted mean difference was used as the combined effect size for continuous variables, while the odds ratio (OR) or risk ratio (RR) was used as the combined effect size for binary variables. Both variables used a 95% confidence interval (CI) to estimate statistical accuracy. In cases with low heterogeneity, the fixed-effects model was used to pool the estimated value; otherwise, the random-effects model was used when significant heterogeneity was detected. Results Fifteen retrospective studies including 5,056 patients who underwent nephrectomy (PN: 1975, RN: 3081) were included. The decline in estimated GFR (eGFR) after PN was lower than RN [(MD: −11.74 ml/min/1.73 m2; 95% CI: −13.15, −10.32; p < 0.00001)]. The postoperative complication rate of PN was higher than that of PN (OR: 2.09; 95% CI: 1.56, 2.80; p < 0.00001)], and the postoperative overall survival (OS) of PN was higher than that of RN (HR: 0.77; 95% CI: 0.65, 0.90; p = 0.002), and tumor recurrence (RR, 0.69; 95% CI: 0.53, 0.90; p = 0.007). No obvious publication bias was found in the funnel chart of the OS rates of the two groups of patients. Conclusions PN is beneficial for patients with T2 renal tumors in terms of OS and renal function protection. However, it is also associated with a higher risk of surgical complications.